Development and Properties of Low-Calcium Fly Ash-Based Geopolymer Concrete - Hardjito, Djwantoro; Rangan, B. Vijaya (2005)
This Research Report describes the first part of the work carried out by the geopolymer research group at Curtin University of Technology. It describes the development and properties of heat-cured low-calcium fly ash-based geopolymer concrete. This Report will be followed by two other Reports describing the long-term properties of geopolymer concrete, and the behaviour of reinforced geopolymer concrete beams and columns.